On the asymptotic distribution of the Koenker?Bassett estimator for a parameter of the nonlinear model of regression with strongly dependent noise - Ivanov, O. V.; Savych, I. M. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We prove that, under certain regularity conditions, the asymptotic distribution of the Koenker - Bassett estimator coincides with the asymptotic distribution of the integral of the indicator process generated by a random noise weighted by the gradient of the regression function.